Synthesis and Structure of Iron(III) Complex with N,N,O-Donor Aroylhydrazones: The Chloride Anion as Hydrogen Bond Acceptor Forming Infinite Chains - Liu*, Huiyan; Gao, Feng; Niu, Dezhong (Asian Journal of Chemistry, 2011)
A new iron(III) complex, [FeL2](Cl)·(CH3OH)0.5 with acyclic tridentate 5-bromo-salicylaldehyde-6-chloro-2-pyridyl hydrazone (HL) has been synthesized and structurally characterized. The crystal structure consists of chains of alternating [FeL2]+ cations and Cl– anions, linked together by N–H···Cl–···H–N hydrogen bonds. Two tridentate monoanionic meridionally spanning ligands form a distorted octahedral N4O2 coordination sphere around the metal ion.